Bacterial contamination of blood and blood components in a tertiary hospital setting in Nigeria - Bolarinwa, Rahman A.; Aboderin, Oladipo Aaron; Odetoyin, Babatunde W.; Adegunloye, Aramide B. (International Journal of Infection Control, 2010)
Active screening of blood donors has practically eliminated viral pathogens during provision of transfusion services; however, transfusion-associated bacterial sepsis remains an important health-care concern. Currently, it is the most frequently reported cause of infectious transfusion-related fatalities. The aim of this study was to determine the prevalence of bacterial contamination in donor blood and/or blood products, and also to identify the isolated microorganism in a semi-urban university teaching hospital setting in Nigeria. The study was carried out at the Obafemi Awolowo University Teaching Hospitals Complex, Ile-Ife, Nigeria over a five-month period (May to September 2009). A total of 162 units of screened blood and blood products consisting of 160 (98.7%) refrigerated packed cells/whole blood and two (1.3%) platelet concentrate were randomly sampled following aseptic procedure. Samples were incubated at 370C for up to 7-days in Brain Heart Infusion growth medium. The identities of the isolated organisms were determined following standard microbiologic techniques. The resistance pattern of isolates to selected antimicrobial agents was also determined by the disc diffusion method. Overall prevalence of bacterial contamination in donated blood bank refrigerated blood is 8.8%. The organisms isolated were Gram-positive, namely, Staphylococcus aureus,coagulase negative staphylococcus, Bacillus sp,and Listeria sp. Resistance of the organisms to the antibiotics ranged from 29% to 100%. Bacterial contamination of blood and blood components for transfusion is common in Nigeria and it is a potential risk for hospital acquired infection. Key Words: bacterial contaminants, hospital-acquired infection, blood/blood components.